P3.210 Estimating the antibody prevalence of herpes simplex virus type 2 among select middle east and north africa populations. (8th July 2017) - Dargham, Soha; Nasrallah, Gheyath; Al-Absi, Enas; Mohammed, Layla; Disi, Rana Al; Noufal, Mariam; Abu-Raddad, Laith
Abstract : Introduction: There are very limited data on herpes simplex virus type 2 (HSV-2) infection in the Middle East and North Africa (MENA). We examined the overall and age-specific HSV-2 antibody prevalence among select MENA populations currently residing in Qatar. Methods: Sera were collected from blood donors attending Hamad Medical Corporation June 2013–2015. Specimens were screened for HSV-2 antibodies using HerpeSelect 2 ELISA IgG kits. All positive and equivocal specimens detecting presence of HSV-2 antibodies were retested for final HSV-2 status using Euroline Westernblot assays. Demographic information included nationality, age, and sex. Age was grouped into 8 bands:≤24, 25–29, 30–34, 35–39, 40–44, 45–49, 50–54, and ≥55. Age-specific trend of HSV-2 infection among Egyptian, Fertile Crescent (Iraq, Jordan, Lebanon, Palestine, and Syria) and Qatari nationals was described and assessed using the Cochran–Armitage test. Results: Sera from 2165 blood donors were tested for HSV-2. Among 132 retested specimens, 66 were confirmed positive. Country-specific HSV-2 prevalence was measured at 5.5% (95% confidence interval (CI) 3.7%–8.2%) for Qataris, 4.5% (95%CI 1.9%–10.0%) for Iranians, 4.2% (95%CI 1.8%–9.5%) for Lebanese, 3.1% (95%CI 1.2%–7.7%) for Sudanese, 3.0% (95%CI 1.4%–6.4%) for Palestinians, 2.2% (95%CI 1.1%–4.3%) for Egyptians, 2.0% (95%CI 1.0%–5.0%) for Syrians, 1.0% (95%CI 0.3%–3.6%) for Jordanians, 0.7% (95%CI 0.1%–3.7%) for Yemenis, and 0.5% (95%CI 0.1%–2.8%) for Pakistanis. Age-specific HSV-2 prevalence was estimated for Egyptians, nationals of the Fertile Crescent, and Qataris. Overall, HSV-2 prevalence increased with age, but the trend was not always statistically significant in these populations. HSV-2 prevalence was significantly higher for females at 9.1% (95%CI 4.7%–16.9%) than males at 2.8% (95%CI 2.2%–3.6%) (χ 2 p-value<0.01). Conclusion: HSV-2 prevalence among MENA nationals was found to be lower than that commonly found in other regions. However, these observed prevalence levels suggest unmet needs for sexual health and control of sexually transmitted infections (STIs) transmission. Programs need to be established to tackle STIs and their disease burden in this region.